Reshmi Dutta-Flanders, The Language of Suspense in Crime Fiction. A Linguistic Stylistic Approach (Altre Modernità, 2019)
Reshmi Dutta-Flanders, The Language of Suspense in Crime Fiction. A Linguistic Stylistic Approach(London, Palgrave Macmillan, 2017, 500 pp. ISBN 978-1-137-47027-0)by Esterino Adami